Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2023)
Table of Content 1. Effect of feeding frequency and adding Moringa seeds to the ratio on growth traits and some blood components in Awassi lambs Mrs. Israa Salim Hayder, Lecturer Muthanna Fathi Abdullah 2. Yellow Maize farmers knowledge and Implementation of Spodoptera Frugiperda Comprehensive Control Strategies and their Sources of Information in Some Villages of Sohag Governorate in The Arab Republic of Egypt Hala Shokry Nosier, Mohamed El-Sayed Zayed , Mohamed Abdel-Fattah El-Sayed 3. Use of the Azoll plant (Azolla pinnata) in Broiler Diets and its effect on the Microbial Content of the Intestine and Carcass Characteristics Dr. Anwar Mohammed Yonis Al-Hamed, Agric-Eng. Nihad Abdul-Aljabbar Al-Husseiny 4. Factors Affecting Farming Sustainability for Farmers at Banger El-Sokar – Region – El-Behira Governorate Dr. Khaled Elsayed Mohamed, Dr. Islam Hassan Sakr, Dr. Ahmed Mamdouh Amer, Dr. Ebtesam Maher Mohamed 5. The impact of the repercussions of the Coronavirus (COVID-19) pandemic on the rural agricultural sector from farmer’s point of view in Egypt Prof. Mamdouh Mohsen El-Ghazaly, Dr. Mohamed Al-Sayed Ahmed Zayed, Dr. Shereen Mohammed Mahmoud Asy 6. Analyzing Essential Imports of Food and Inputs by Using Descriptive Analysis and Time Series Models (2002-2021) (Adjusted Exponential Smoothing Method) Dr. Amin Osama Shammout, Dr. Osama Suliman Alsalaheen, Dr. Ameen Sulieeman Alzubaidi 7. Improving growth characteristics, quantitative & qualitative characteristics of carcass meat of male Awassi lambs using palm oil Mr. Ahmed Hussein Kuttar, Prof. Mahfoodh Khaleel Abdullah 8. Study of correlation coefficients in the productive performance of different groups in feathers color and egg quality characteristics in quail Asst-Lecturer / Haytham Mohammed Sabeeh Hadi